Graphene Films: Synthesis of Graphene Films on Copper Foils by Chemical Vapor Deposition (Adv. Mater. 29/2016). Issue 29 (1st August 2016) - Li, Xuesong; Colombo, Luigi; Ruoff, Rodney S.
Abstract : Synthesis of graphene films on copper foils is discussed by X. Li, L. Colombo, and R. S. Ruoff on page 6247. Graphene can grow on metal substrates by chemical vapor deposition of hydrocarbons. Hydrocarbons crack on a metal surface, nucleate, grow, and finally merge to form a continuous graphene film. Copper is one of the best candidates for graphene growth due to the advantages of good control over the graphene thickness, the growth of high‐quality graphene, and the ease for graphene transfer, and has been widely used for production of large‐area graphene films in both academia and industry.